A Study on the Emotional Intelligence and Adjustment among Senior Secondary Students: Exploring the Link between Emotional Intelligence and Adjustment in Senior Secondary Students (Journal of Advances and Scholarly Researches in Allied Education, 2017)
Emotional Intelligence is an articulation that joins the confusing pieces of both feeling and intelligence. Feelings rule the heart while intelligence reigns extraordinary in the mind. The twin attributes are indistinguishable and they practice massive impact in the ordinary every day presences of individuals. By and by, intelligence and achievement are not seen a similar way they were at that point. New theories of intelligence have been shown and are a tad at any given moment replacing the customary hypothesis. Today, the entire understudies have changed into the purpose of assembly of concern, his reasoning breaking points, yet additionally his innovativeness, feeling and social capacities. IQ alone is no more the rule measure for progress, emotional intelligence social intelligence and karma in like way anticipate an essential occupation in the individual achievement and change. Today there are heaps of social issues like stress, modification, achievement, etc. are central worries among the secondary school pack which we are watching reliably. Specialists have induced that individuals who manage their own one of a kind feelings well and oversee others will undoubtedly live substance lives. This Paper shows the relationship between Emotional Intelligence and adjustment among senior secondary students.